Environmental Goals Addressed in Assessments of Contaminated Sediments. (19th December 2019) - Bruce, Peter; Ohlsson, Yvonne
ABSTRACT: Environmental management often aims at sustainability and at implementing goals such as the United Nations Sustainable Development Goals (SDGs). Several of these goals rely upon healthy sediments, implying that contaminated sediments need to be addressed in environmental management. In Sweden, the SDGs and national environmental objectives are meant to be central in environmental management. However, in environmental risk assessment (ERA) for contaminated sediments, it is not clear to assessors or authorities in Sweden which goals to consider and how. In the present study, we explore which environmental goals ERAs of contaminated sediment should consider, according to representatives from Swedish regulatory and advisory authorities, and to what extent ERAs consider those goals in practice in Sweden. The identified goals indicated that protection of aquatic ecosystems and associated services is a main priority for the authorities. The ERAs analyzed showed that most identified goals were addressed, albeit not consistently. Furthermore, risk assessors seem to put less weight on ecological aspects than authorities do. This indicates that authorities need to stress the importance of environmental aspects and provide guidance on how to address them. Several environmental goals were found to be directly relevant to contaminated sediments and ERAs can contribute to their fulfillment, given that ERA is a basis for management decisions. However, practitioners need clearer guidance on which goals to address and how. Finally, there seems to be good potential for implementation of the SDGs in environmental management in Sweden, due to existing legislation based on sustainable development and well‐anchored national environmental objectives that overlap with the SDGs. Integr Environ Assess Manag 2019;00:1–12. © 2019 The Authors. Integrated Environmental Assessment and Management published by Wiley Periodicals, Inc. on behalf of Society of Environmental Toxicology & Chemistry (SETAC) KEY POINTS: Sweden aims at taking the lead toward the sustainable development goals (SDGs), yet for environmental risk assessments (ERAs) of contaminated sediments the authorities do not yet require assessors to address such goals; neither are there any official guidelines on how to address them. We have identified a set of environmental objectives and SDGs that authorities consider directly relevant for stakeholders to address when assessing risks from contaminated sediments. The set of goals indicates that the scope of ERA in Sweden has to be broader to include sustainable management of ecological functions and ecosystem services in addition to the prevalence of contaminants and human health risks. This study indicates that ERA in a Swedish context is in a good position to potentially contribute more to several of the goals identified as relevant than is contributed today, with guidance and cooperation with the authorities.